2011
DOI: 10.1177/0021998311423860
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance and modelling of a fully recycled modified CF/PP composite

Abstract: A fully recycled carbon fiber reinforced maleic anhydride grafted polypropylene (MAPP)-modified polypropylene (rCF/ rPP) composite material has been developed and characterized. This new composite was manufactured employing papermaking principles, dispersing the recycled carbon fibers (rCF) in water, and forming them into mats. Two layers of the recycled polypropylene (rPP) films manufactured using press-forming were sandwiched between three rCF preform layers in a stack. The stack was heated and press-formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The comparative plots are provided in Figure 9 below. The plots demonstrate good correlation with about 5% error when compared to the results obtained by Szpieg et al [27]. Therefore, the modelling approach Figure 8.…”
Section: Model Validationsupporting
confidence: 68%
See 3 more Smart Citations
“…The comparative plots are provided in Figure 9 below. The plots demonstrate good correlation with about 5% error when compared to the results obtained by Szpieg et al [27]. Therefore, the modelling approach Figure 8.…”
Section: Model Validationsupporting
confidence: 68%
“…Findings based on the FEA study conducted suggest that CFRP composite material offers good resistance to thermal stress, even at elevated temperatures up to 800 K. The results were compared with Al-Qrimli et al [28] and Szpieg et al [27], and a good correlation was observed. However, it is recommended to conduct experiments to further validate the numerical results.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Thermoplastic rCF compounds for injection molding (Connor 6 and Kreibe 22 ) and compression molding of semifinished products, such as rCF BMC and sheet molding compound (SMC) (e.g. Allen, 8 Turner et al, 9,14 Pickering et al, 12 Szpieg et al 23 ), were thoroughly researched. The first SMC parts made of rCF are already in application, for example, in the BMW 7 series.…”
Section: Introductionmentioning
confidence: 99%